ETHICAL LITERARY CRITICISM; KAZUO ISHIGURO’S WORKS THROUGH ETHICAL PERSPECTIVES - Komilova Liliya Maratovna (Journals Park Publishing, 2024)
Ethical literary criticism can be described as an approach to interpreting modern English literature, offering readers a chance to explore the moral complexities and ethical dilemmas of the stories that shape our understanding of the world. As we learn the different types of contemporary literary works, we face with characters, themes, and narratives that present profound ethical dilemmas and challenge us to reflection the human choices. This research analyzes Ishiguro’s works through ethical side, analyzing the ethical dilemmas faced by his characters, the ethical responsibilities of authorities, and the societal reflections described within his narratives.
Keywords: literary criticism, ethical literary criticism, moral critique, fiction, novel, organ donors, euthanasia.